Glass-based biosensing device for monitoring CA15-3 cancer biomarker - Truta, Liliana (2019)
We thank funding to the European Research Council, through the Starting Grant 3P’s (GA311086, given to MGFS) and to Norte 2020 - Programa Operacional Regional do Norte, through the project CANCER (NORTE-01-0145-FEDER-000029). The authors also thank due to CICECO-Aveiro Institute of Materials, POCI-01-0145-FEDER-007679 (FCT Ref. UID/CTM/50011/2013).